A Bayesian framework for the expectations hypothesis.: How to extract additional information from the term structure of interest rates - Andrea Carriero (Queen Mary University of London, Department of Economics, 2007)
Even if there is a fairly large evidence against the Expectations Hypothesis (EH) of the term structure of interest rates, there still seems to be an element of truth in the theory which may be exploited for forecasting and simulation. This paper formalizes this idea by proposing a way to use the EH without imposing it dogmatically. It does so by using a Bayesian framework such that the extent to which the EH is imposed on the data is under the control of the researcher. This allows to study a continuum of models ranging from one in which the EH holds exactly to one in which it does not hold at all. In between these two extremes, the EH features transitory deviations which may be explained by time varying (but stationary) term premia and errors in expectations. Once cast in this framework, the EH holds on average (i.e. after integrating out the effect of the transitory deviations) and can be safely and effectively used for forecasting and simulation.
Keywords: C11; E43; E44; E47; 330; Bayesian VARs; Expectations theory; Term structure; Zinsstrukturtheorie; Bayes-Statistik; VAR-Modell; Prognoseverfahren